Epitaxial growth of NbN thin films for electrodes using atomic layer deposition - Young Jang, Seo; Min Lee, Hye; Young Sung, Ju; Eun Kim, Se; Deock Jeon, Jae; Yun, Yewon; Mo Moon, Sang; Eun Yoo, Joung; Hyeon Choi, Ji; Joo Park, Tae; Woon Lee, Sang (Applied Surface Science, 2023)
The epitaxial growth of NbN thin film was accomplished via atomic layer deposition (ALD) for the first time using NbCl5 and NH3 as the Nb precursor and nitrogen source at a deposition temperature of 450 ℃. The cubic NbN thin film was grown epitaxially on a cubic MgO crystal through the coherent lattice matching between NbN and MgO with a small lattice mismatch (∼2.8%). A high concentration of Cl impurity of 4–5% remained in NbN thin films grown on a SiO2 substrate using ALD. However, the Cl impurity concentration decreased to ∼ 2% in the epitaxially grown NbN thin films, which facilitated the epitaxial growth of NbN thin films on the MgO substrate. The origin was attributed to a residual strain at the NbN/MgO interface, which induced a bond length change in Nb-N-Cl. The bond length change may promote Cl desorption during NbN ALD because an in-plane compressive strain in the NbN film and an in-plane tensile strain in the MgO surface were observed. Finally, the epitaxially grown NbN thin film exhibited a 50% lower resistivity than that grown with a polycrystalline phase based on the enhanced carrier mobility owing to the improved crystallinity of epitaxial NbN thin films.
Keywords: Atomic-layer deposition; Coherent lattice; Deposition temperatures; Epitaxially grown; Impurities concentration; Lattice matching; Metal thin film; MgO crystals; NbN thin film; Nitrogen sources; Atomic layer deposition; Epitaxy; Lattice matching; Metal thin film; NbN